Teaching Creative Writing Online. - Beck, Heather (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2004)
This paper discusses experiences of teaching a Masters degree in Creative Writing online with WebCT Software. Discussion is set out as follows: course structure, how the course runs online, initial concerns when adapting the course to run online, Salmon's five-stage model for teaching and learning online, disadvantages of teaching online and advantages of teaching online. The paper concludes with further plans for developing a model for teaching and learning creative writing online.